ANALISIS DAMPAK SOSIAL DAN EKONOMI KEBERADAAN EMBUNG DI DESA TOLINGGULA PANTAI KECAMATAN TOLINGGULA KABUPATEN GORONTALO UTARA - Inong Thalib Uriasi; Mahludin Baruadi; Irwan Bempah (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This research was conducted with the aim of: 1). To describe the social impact on the community regarding the existence of the North Gorontalo reservoir. 2). To describe the economic impact on the community regarding the existence of the North Gorontalo reservoir. The research method used is descriptive with the type of qualitative research. The data used are sourced from primary data obtained from interviews and secondary data obtained from publications relevant to the study. The results of this study indicate that: 1). The social impact of the existence of the dam is to make the relationship between the community closer, especially the farmers because they always work together, help each other and work together with other farmers. This mutual cooperation activity in Tolinggula Beach Village, Tolinggula District is known as "Molude" (planting). 2). The economic impact on the existence of the reservoir is the existence of job opportunities and large business opportunities for the community as well as increased income and acceleration of infrastructure development such as the construction of access roads to the location of the reservoir.